1988
DOI: 10.1093/geronj/43.1.m18
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age On Serum Albumin in Healthy Males: Report From The Normative Aging Study

Abstract: To clarify the relation between age and serum albumin, measures were obtained on a screened population of 1066 healthy males in the Normative Aging Study. Multiple regression analysis shows only a slight decline in albumin of 0.054 gm/dl per decade with R = -0.12 (p less than .001) on cross-sectional data. This small decline occurs entirely within the range of normal, contrary to many previous reports. Mean albumin values were 4.25 (+/- .26 SD) for subjects in the eighth decade and 4.13 (+/- .29 SD) in the nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 0 publications
4
36
1
1
Order By: Relevance
“…However, such slopes were higher than previous reports as Ϫ0.0054 to Ϫ0.0095 per year (13,16,27). As a possible explanation for this disagreement, we consider that some previous studies had confounded aging effect on the mixed morbid and healthy cohort.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…However, such slopes were higher than previous reports as Ϫ0.0054 to Ϫ0.0095 per year (13,16,27). As a possible explanation for this disagreement, we consider that some previous studies had confounded aging effect on the mixed morbid and healthy cohort.…”
Section: Discussioncontrasting
confidence: 74%
“…In addition to disease-related malnutrition, age-related changes such as metabolism, dietary intake, physical activity and body composition are supposed to influence the nutritional status indicated with serum albumin. Several studies excluded patients with malnutrition, protein-losing enteropathies, myeloma, renal or hepatocellular disease to define age-related trends in serum albumin (15,16). Another study adjusted demographic, health behavior and health status to examine the independent factors of age and serum albumin simultaneously (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study (Campion et al, 1988) indicated that in healthy male subjects the serum albumin level did not change at all with increasing age.…”
Section: Introductionmentioning
confidence: 90%
“…There is a reduction in blood albumin concentration of about 10% in older people (Greenblatt, 1979;Campion et al, 1988) and possibly an increase in ␣1-acid glycoprotein (Verbeeck et al, 1984), probably secondary to age-associated inflammatory disease (Grandison and Boudinot, 2000). This decrease of albumin has been reported to be associated with an increase in the unbound fraction of many drugs including phenytoin (Patterson et al, 1982), diazepam (Davis et al, 1985), and piroxicam (Boudinot et al, 1993), but not of prazosin (Andros et al, 1996), warfarin (Shepherd et al, 1977), and verapamil (Schwartz et al, 1994).…”
Section: B Volume Of Distribution and Agingmentioning
confidence: 99%